Does handedness matter? Writing and tracing kinematic analysis in healthy adults - Ivančević Nikola; Novičić Marija; Miler-Jerković Vera; Janković Milica; Stevanović Dejan; Nikolić Blažo; Popović Mirjana B.; Jančić Jasna (Psihologija, 2019)
Writing is a complex skill and it can be affected by many factors. One of the most obvious is handedness. The actual influence of handedness (especially left-handedness, since almost 10% of the population is left-handed) onto writing performance has not been fully studied in previous research. Digitalized kinematic analyses and assessments of writing strategies (i.e., graphic rules and principles) are two approaches to investigating writing characteristics poorly addressed in previous research. The aim of this study was to analyze the effects of handedness onto writing kinematics using the aforementioned approach. The study included 34 young healthy adults (of whom 11 were left-handed) performing three writing tasks on a digital board. The tasks included semicircle and figure tracing and cursive letter writing. Regarding kinematics, left-handers performed tracing movements with higher mean horizontal acceleration and lower mean horizontal jerk compared to right-handed subjects. In addition, the left-handed wrote less accurately (i.e., undershooting more writing borders) and made more pauses during the letter writing task. The obtained results suggest that handedness slightly affects writing performance, and since left- and right-handers use the same cognitive strategies to writing and tracing, the observed differences could be mainly due to biomechanical constraints, what needs further studies in more representative samples. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 175016]